Quality and Composition Analysis of Meat and Meat Products - Mohinur Umarova; Shokhsanam Umurzakova (European Science Publishing, 2023)
In this article, the quality of meat and the products grown from it, i.e. morphologically, meat includes muscle tissue, fat, connective tissue, bones and nerve fibers, the most valuable of minerals are phosphorus, sodium, potassium, magnesium and iron. Information about salts is given.